2023
DOI: 10.7759/cureus.35423
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of ICU Mortality Scoring Systems Applied to COVID-19

Abstract: BackgroundOver the past three years, COVID-19 has been a major source of mortality in intensive care units around the world. Many scoring systems have been developed to estimate mortality in critically ill patients. Our intent with this study was to compare the efficacy of these systems when applied to COVID-19. MethodsThe was a multicenter, retrospective cohort study of critically ill patients with COVID-19 admitted to 16 hospitals in Texas from February 2020 to March 2022. The Simplified Acute Physiology Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Consistent with other studies, [33,34] on the third day of ICU admission, morbidity was associated with the higher need for FIO2, more frequent hypotension, and consequently a higher need for inotropes. Both the need for muscle relaxants and the use of the prone position were more common in patients with higher mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with other studies, [33,34] on the third day of ICU admission, morbidity was associated with the higher need for FIO2, more frequent hypotension, and consequently a higher need for inotropes. Both the need for muscle relaxants and the use of the prone position were more common in patients with higher mortality.…”
Section: Discussionsupporting
confidence: 90%
“…A BMI > 40 kg/m 2 was associated with almost double the COVID-19-related mortality compared to patients without obesity. In the ICU setting, several studies [24,33,34] have reported an association between increased incidence of adverse prognosis and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The SOFA score executed the best. The study conducted by our team showed correlations of the values obtained in the SOFA, APACHE II, and SAPS II scales with mortality 12 .…”
Section: Discussionmentioning
confidence: 79%
“…There are many studies on the effect of Ang-II and its blockers on the course of COVID-19 infection; however, there is still uncertainty about the role of aldosterone 12 . Higher aldosterone levels were showed to be associated with COVID-19 severity (measured by maximal ordinal scale) 9 .…”
Section: Introductionmentioning
confidence: 99%